Impact of egg incubation on hemocyte recruitment and susceptibility of Galleria mellonella larvae to pathogens - Carmo, Paulo Henrique Fonseca; de Lima, Patrícia Michelle Nagai; Silva, Fabiana Alves; Ribeiro, Jaqueline Lemes; Junqueira, Juliana Campos; Garcia, Maíra Terra (Frontiers in Microbiology, 2025)
IntroductionGalleria mellonella is widely used as an in vivo model in microbiological and toxicological studies due to its reproducibility, low cost, and ease of handling. However, maintaining homogeneous laboratory colonies presents challenges. This study evaluated whether different incubation methods influence the larval immune response against Staphylococcus aureus, Candida albicans, and Escherichia coli.MethodsFour experimental groups were established: (1) Traditional group (TG), eggs stored at 27°C; (2) Immediate group (IG), eggs stored at 16°C for 120 days before incubation at 27°C; (3) Gradual group (GG), temperature gradually reduced from 27°C to 16°C over 98 days, then increased back; and (4) Frozen group (FG), eggs stored at freezing temperatures.Results and discussionFG eggs were non-viable, and IG and GG showed delayed development. IG larvae were more susceptible to infections, while GG larvae resembled TG. Thus, GG can serve as an effective alternative rearing method.